2019
DOI: 10.1039/c9nr02597a
|View full text |Cite
|
Sign up to set email alerts
|

Ni2P promotes the hydrogenation activity of naphthalene on wrinkled silica nanoparticles with tunable hierarchical pore sizes in a large range

Abstract: Herein, a series of wrinkled silica nanoparticles with hierarchical pores (HPWSNs) were successfully prepared by dual-templating, of which the Ni2P/HPWSNs-0.13 catalyst with the smallest Ni2P particles exhibited the highest naphthalene hydrogenation activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…The predicted adsorption configurations were flat, in line with the above speculations and previously reported results. [8] The negative values of E ads indicated that the adsorption of NAP and tetralin was spontaneous and exothermic (Table S5, Supporting Information), in line with other reports on non-oxide compounds. [8] The energy of NAP adsorption on the pure α-MoC (i.e., α-MoC-1 and α-MoC-2) surface ranged from −170 to −196 kJ mol −1 .…”
Section: Insights Into Surface Structure-performance Relationshipsupporting
confidence: 88%
See 3 more Smart Citations
“…The predicted adsorption configurations were flat, in line with the above speculations and previously reported results. [8] The negative values of E ads indicated that the adsorption of NAP and tetralin was spontaneous and exothermic (Table S5, Supporting Information), in line with other reports on non-oxide compounds. [8] The energy of NAP adsorption on the pure α-MoC (i.e., α-MoC-1 and α-MoC-2) surface ranged from −170 to −196 kJ mol −1 .…”
Section: Insights Into Surface Structure-performance Relationshipsupporting
confidence: 88%
“…[8] The negative values of E ads indicated that the adsorption of NAP and tetralin was spontaneous and exothermic (Table S5, Supporting Information), in line with other reports on non-oxide compounds. [8] The energy of NAP adsorption on the pure α-MoC (i.e., α-MoC-1 and α-MoC-2) surface ranged from −170 to −196 kJ mol −1 . The energy of NAP adsorption on Mo vacancy sites (Mo(v)-A, −220 kJ mol −1 ) was much higher (in absolute terms) than that on the α-MoC surface, which indicated stronger adsorption in the former case (peak 3).…”
Section: Insights Into Surface Structure-performance Relationshipsupporting
confidence: 88%
See 2 more Smart Citations
“…In recent years, Ni 2 P catalysts have shown high intrinsic hydrogenation activity in hydrodesulfurization [9,10] and hydrodenitrogenation reactions [11,12] due to their special crystal morphology and physicochemical properties, and they are expected to be the new generation of highly efficient aromatic hydrosaturation catalysts [13,14]. Unlike metal carbides and nitrides, the radius of P atoms (0.109 nm) is much larger than that of C atoms (0.071 nm) and N atoms (0.065 nm).…”
Section: Introductionmentioning
confidence: 99%